POTENSI DANAU BIRU SEBAGAI IKON DESA WALASIHO MENJADI DESA WISATA DI KOLAKA UTARA - La Ode Mahmud; Bakti; Wa Ode Haliyanti Unga; Akbar Wahbi (Journal Publicuho, 2024)
This study investigates the potential of Walasiho Village, with Biru Lake as its main attraction icon, to be developed into a superior tourism village. Using quantitative descriptive analysis to analyze the feasibility score of Walasiho Village into a tourism village that includes indicators such as attractions, accessibility, facilities, and additional services, Walasiho Village achieved a score of 70.50, indicating its feasibility for tourism village development. SWOT analysis to measure the internal and external environment identifies key strengths, including the natural beauty of Biru Lakes, strong community support, and opportunities such as local government support and high public interest in tourism. However, drawbacks such as inadequate facilities and a lack of innovative attractions are also noted. The study recommends the need for strategic initiatives to address these weaknesses, including capacity building and infrastructure upgrades. The impact of the COVID-19 pandemic on the tourism sector has further demonstrated the need for resilient and adaptive strategies. This research contributes to the understanding of rural tourism development and provides actionable recommendations for sustainable development, local economic development, and community welfare in Walasiho village. Future research should explore the long-term effects of tourism development on local communities and evaluate the success of strategies implemented.